A Study to Evaluate Serum Creatinine Phosphokinase and Serum Lactate Dehydrogenase as A Potential Prognostic Marker in Assessing Clinical Severity with Organophosphorus Poisoning - Reddy, Chittamuru Maansi; Prabhakar K, Prabhakar K; Vidyasagar, Vidyasagar; Anitha, Anitha; Prabhavathi K, Prabhavathi K (Journal of Neonatal Surgery, 2025)
Background: Organophosphorus (OP) poisoning remains a significant public health concern, particularly in regions where pesticides are widely used. OP compounds function as irreversible inhibitors of cholinesterase enzymes, leading to severe neurological, cardiovascular, and respiratory complications. Early identification of high-risk patients is crucial for optimizing treatment strategies and improving outcomes. This study aims to evaluate the prognostic significance of serum creatinine phosphokinase (CPK) and lactate dehydrogenase (LDH) levels in assessing the clinical severity of OP poisoning using the Peradeniya Organophosphorus Poisoning (POP) scale. Methods: This prospective observational study was conducted over a 3-month period at RLJH Hospital, including 30 patients diagnosed with acute OP poisoning. Inclusion criteria encompassed patients aged ≥18 years, presenting with clinical symptoms of OP poisoning, and admitted to intensive care. Exclusion criteria included pre-existing neuromuscular, metabolic, or cardiovascular conditions. Blood samples were collected at admission for serum CPK and LDH estimation using an automated bioanalyzer. The severity of poisoning was classified using the POP scoring scale, and patients were categorized into mild (0–3), moderate (4–7), and severe (8–11) groups. Statistical analyses, including Pearson correlation, chi-square test, and regression models, were used to assess the relationship between biomarker levels and clinical severity. Results: Elevated serum CPK and LDH levels showed a strong positive correlation with higher POP scores, indicating greater poisoning severity (p < 0.05). Patients in the severe category exhibited significantly higher CPK and LDH values than those in the mild and moderate groups. ROC curve analysis demonstrated that CPK had a higher predictive accuracy for severe OP poisoning than LDH, making it a potential early biomarker for risk stratification. Conclusion: Serum CPK and LDH levels serve as cost-effective and accessible prognostic markers for assessing the severity of OP poisoning. Their integration into clinical evaluation may help improve early risk identification, guiding timely interventions, especially in resource-limited settings. Further studies with larger cohorts are warranted to validate these findings and establish standardized biomarker thresholds for OP poisoning management.